2017
DOI: 10.1111/jnc.14117
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and metabolism of sulphated steroids by the blood–brain barrier in the adult male rat

Abstract: Little is known about the origin of the neuroactive steroids dehydroepiandrosterone sulphate (DHEAS) and pregnenolone sulphate (PregS) in the brain or of their subsequent metabolism. Using rat brain perfusion in situ, we have found 3 H-PregS to enter more rapidly than 3 H-DHEAS and both to undergo extensive (> 50%) desulphation within 0.5 min of uptake. Enzyme activity for the steroid sulphatase catalysing this deconjugation was enriched in the capillary fraction of the blood-brain barrier and its mRNA express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 81 publications
1
21
0
Order By: Relevance
“…However, in the earlier study, Wang et al [81] demonstrated the transport of peripherally applied pregnenolone sulfate across the BBB, which was approximately ten times slower when compared to the unconjugated pregnenolone. A recent study by Qaiser et al [82] also demonstrates an uptake of peripherally applied [ 3 H]-DHEAS and [ 3 H]-PregS, which is more rapid for the latter (less polar) conjugate. A consequent extensive (>50%) desulfation of both conjugates within 0.5 min of uptake was observed.…”
Section: Anti-glucocorticoid Immunoprotective Steroidsmentioning
confidence: 89%
“…However, in the earlier study, Wang et al [81] demonstrated the transport of peripherally applied pregnenolone sulfate across the BBB, which was approximately ten times slower when compared to the unconjugated pregnenolone. A recent study by Qaiser et al [82] also demonstrates an uptake of peripherally applied [ 3 H]-DHEAS and [ 3 H]-PregS, which is more rapid for the latter (less polar) conjugate. A consequent extensive (>50%) desulfation of both conjugates within 0.5 min of uptake was observed.…”
Section: Anti-glucocorticoid Immunoprotective Steroidsmentioning
confidence: 89%
“…The sulphatase pathway in the CNS is relevant because (although recent studies are revisiting this paradigm; Qaiser et al, 2017 ), sulphated-steroids do not cross the blood-brain barrier. Therefore, sulphated neurosteroids like DHEA-S and P5-S need to be generated locally, and in line with this, their level in the CNS is independent from the level in the blood (Rajkowski et al, 1997 ) and varies throughout distinct brain regions (especially hippocampus and hypothalamus) (Jäntti et al, 2010 ).…”
Section: Intracrinology In Peripheral Tissuesmentioning
confidence: 99%
“…Although sulphated steroids such as DHEAS and pregnenolone sulphate may enter the brain through circulation via organic anion transporting peptides (OATP) transporting them both ways, it would appear that OATP transport of sulphated steroids favours movement out of the CNS, not in [ 155 ]. However, a recent study investigating the transport of DHEAS and PREGS through the blood brain barrier (BBB) of rats found that although PREGS entered the blood brain barrier more readily, DHEA was rapidly metabolised into androstenedione and androstenediol [ 156 ]. Further investigation found that the enzymes responsible for the rapid desulphatasion were mainly localised the BBB capillaries as opposed the brain parenchyma [ 156 ].…”
Section: Potential Mechanisms For Dhea-mediated Neuroprotective Effecmentioning
confidence: 99%
“…However, a recent study investigating the transport of DHEAS and PREGS through the blood brain barrier (BBB) of rats found that although PREGS entered the blood brain barrier more readily, DHEA was rapidly metabolised into androstenedione and androstenediol [ 156 ]. Further investigation found that the enzymes responsible for the rapid desulphatasion were mainly localised the BBB capillaries as opposed the brain parenchyma [ 156 ]. This argues that the DHEA in brain is likely from peripheral sources as opposed to de novo synthesis.…”
Section: Potential Mechanisms For Dhea-mediated Neuroprotective Effecmentioning
confidence: 99%